There is nothing like a thane! : the lighter side of Macbeth - Francis, Clive, 1946-; Shakespeare, William, 1564-1616. (New York : Thomas Dunne Books, 2003)
A compilation of unintentional funny moments from a variety of productions of William Shakespeare's "Macbeth".
Includes index.
Young Adult
Keywords: Macbeth, -- King of Scotland, -- 11th cent. -- In literature -- Anecdotes; Macbeth, -- King of Scotland, -- 11th cent. -- In literature -- Anecdotes; Shakespeare, William, -- 1564-1616. -- Anecdotes; Shakespeare, William, -- 1564-1616. -- Anecdotes; Scotland in literature -- Anecdotes; Scotland -- In literature -- Anecdotes